تسعير منتجات الشركات التي تمارس التسويق الدولي عبر الإنترنت - ديوب, محمد عباس; أحمد, أحمد صقر; سليمان, نبيلة (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يتناول هذا البحث موضوع تسعير منتجات الشركات التي تمارس التسويق الدولي عبر الإنترنت، ويوضّح مفهوم التسعير والعوامل المؤثرة في تحديد السعر وأثر الإنترنت على كل عامل منها. فالإنترنت تخفّض التكاليف التي تتحملها الشركات, ممّا يساعدها على تخفيض أسعارها. كذلك فإن المنافسة الشديدة التي تواجهها الشركات على الإنترنت تؤدي إلى الضغط عليها لتخفيض أسعارها، فالأسعار المنخفضة على الشبكة تعتبر أهمّ دوافع المستهلكين للشراء عبرها. وبفضل الإنترنت لم تعد هناك مشكلة جغرافية أو نقص في المعلومات بالنسبة لأي مستهلك، كما أنها منحته القوة ممّا شجع المستهلكين على استخدام هذه الشبكة وأدّى إلى اتساع سوقها الذي ما زال يتزايد باستمرار. وتناولنا أيضاً الطرق التي يمكن إتّباعها لوضع السعر حيث إن كل شركة تختار ما يناسبها منها، ومن ثم أجرينا مقارنةً بين التسعير الدولي التقليدي والتسعير الدولي عبر الإنترنت، وفي النهاية تمّ تقديم أهمّ النتائج التي تمّ التوصل إليها والمقترحات بخصوص التسعير عبر الإنترنت. We study in this research the pricing of products by companies that perform international marketing via the internet. We clarify the concept of pricing and the factors affecting it, including that of the internet. The internet decreases the costs that the companies bear, leading to a decrease of prices. Moreover, strong competition among companies on the internet forces them to cut down prices, because the low price on the internet is the most important motive for the consumers to use for buying. The geographic boundaries and the lack of data are no longer a problem for any consumer. The internet gave the customer the strength, which encouraged him to use it, and that, in turn, led to a growing internet market. We also study the ways used for pricing, because each company chooses the way that suits it. We then make a comparison between traditional international pricing and international pricing via internet. Finally, we present our results and offer some recommendations concerning pricing via internet.